2020
DOI: 10.1002/ecy.3212
|View full text |Cite
|
Sign up to set email alerts
|

Woody plant growth increases with precipitation intensity in a cold semiarid system

Abstract: As the atmosphere warms, precipitation events become larger, but less frequent. Yet, there is fundamental disagreement about how increased precipitation intensity will affect vegetation. Walter's two‐layer hypothesis and experiments testing it have demonstrated that precipitation intensity can increase woody plant growth. Observational studies have found the opposite pattern. Not only are the patterns contradictory, but inference is largely limited to grasslands and savannas. We tested the effects of increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
0
19
3
Order By: Relevance
“…Consistent with previous observational studies that found winter wheat to be resistant to changes in precipitation intensity [18,26], we found no response of winter wheat to a wide range of precipitation intensity treatments. This is in contrast to the findings of a paired study in a nearby rangeland site that used the same methods and experimental design, and that documented increased shrub growth in response to these same increased precipitation intensity treatments [10]. Our result that winter wheat was not responsive to treatments was consistent across all above-and belowground physiological and biomass measurements, including grain yield.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Consistent with previous observational studies that found winter wheat to be resistant to changes in precipitation intensity [18,26], we found no response of winter wheat to a wide range of precipitation intensity treatments. This is in contrast to the findings of a paired study in a nearby rangeland site that used the same methods and experimental design, and that documented increased shrub growth in response to these same increased precipitation intensity treatments [10]. Our result that winter wheat was not responsive to treatments was consistent across all above-and belowground physiological and biomass measurements, including grain yield.…”
Section: Discussioncontrasting
confidence: 99%
“…The experimental design generally followed that of Holdrege et al [10]. Broadly, precipitation was collected and redeposited as larger events of fixed sizes (i.e., 1 to 18 mm) so that all plots received the same total amount of precipitation, but that precipitation was deposited as either many small or few large events.…”
Section: Experimental Designmentioning
confidence: 99%
See 3 more Smart Citations